La migración interna contemporánea en Antioquia desde la perspectiva de la teoría de sistemas (2014)
ABSTRACT: The objective of this article is to present an analysis of the internal migration under the scope of Niklas Luhmann’s social system theory, added to Marcel Mauss’s gifts intending to contribute with elements that help in the analysis of this social phenomenon, the components and operations of an inter-intra regional migration system. The investigation was conducted in the Department of Antioquia Colombia, in its capital city and villages, seeking to unravel the logic of the population mobility not only in their arrival to the cities but in their continuous interrelation with their native regions.